Pome polishing treatment using palm kernel shell activated carbon produced via industrial kiln - Abd. Fatah, Rugayah (2017)
Malaysia is one of the largest producers and exporters of palm oil products in the Asian region. To manage the waste generated from palm oil processing is not easy as some of palm oil mills still fail to comply with the standard discharge limit set by Department of Environment even though biologically treatment unit has been applied. Hence, in this study polishing treatment unit was proposed using adsorption process that improved the 3-days biological oxygen demand (BOD3), chemical oxygen demand (COD), suspended solid (SS) and colour removing efficiency so that the standard discharge limit can be achieved. The potential of palm kernel shell (PKS) based activated carbon (AC) as adsorbent in removal of organic matters in palm oil mill effluent (POME) was investigated. The precursor was prepared in a large scale environmental charcoal kiln by carbonization under controlled atmosphere and physically activated using large scale rotary kiln using the optimum parameter (steam injection at 5L h-1; temperature 900-1000 oC). The largest Brunauer-Emmett-Teller (BET) surface area of palm kernel shell activated carbon (PKS AC) obtained was 607.8 m2/g with the pore volume of 0.25 cm3/g. The optimum condition to reduce BOD3 to 17 mgL-1 was 50 g/250 mL PKS AC, 24 h mixing time, 150 rpm and at pH 2 whereas COD, SS, and colour value obtained after polishing treatment were 203 mg/L, 145 mg/L and 2640 Pt-Co, respectively. The adsorption equilibrium was best represented by Langmuir and Freudlich isotherm model whilst the kinetics of adsorption was well described by pseudo-first order model. Regeneration study was carried out by thermal treatment. The adsorption capacity for organic matters was 6.08-4.36 mg/g, after five adsorption-regeneration cycles. This study has identified that PKS AC has a potential to be used as a precursor in the preparation of AC to achieve BOD3 of less than 20 mgL-1 in POME polishing treatment.